Simulation platform for microgrid based on photovoltaic generation. (1st January 2012) - Wang, Xiaohui; Wang, Jing; Wang, Jia
A simulation platform for research of microgrid dynamic characteristics is established based on photovoltaic (PV) generation in this paper. The PV cell module and power grid are set up according to their operation principles, and the constant power control strategy is utilised to the inverter of PV generator. PV cells operating in grid-connected mode and islanding mode are simulated under the software respectively and the simulation results of power, voltage and frequency can provide basis for the operation and design of microgrid system.